2022
DOI: 10.1002/jmv.27606
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress status and vitamin D levels of asymptomatic to mild symptomatic COVID‐19 infections during the third trimester of pregnancy: A retrospective study in Metz, France

Abstract: It is believed that the subtle equilibrium between tolerance and immunity during the unique biological state of pregnancy, which is characterized by further physiological and hormonal changes, rends pregnant women more vulnerable to coronavirus disease 2019 . In this retrospective study, confirmed COVID-19-positive pregnant women (n = 15) during their third trimester, comprising asymptomatic (n = 7) and mild symptomatic (n = 8), and healthy pregnant controls (n = 20), were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 37 publications
(102 reference statements)
1
23
0
Order By: Relevance
“…This suggests an alteration in the systemic redox status [ 8 ]. In another retrospective study in France by Schmitt et al that enrolled 15 pregnant women with and without COVID-19 during their third trimester, no differences were shown between CRP levels and OS markers between groups [ 30 ]. Another report from Iran by Karkhanei et al including 96 individuals with and without COVID-19 found that elevation in serum levels of OS (reduced glutathione and TAC) and reduction of antioxidant indices (total oxidant status) could aggravate the disease's severity in hospitalized patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests an alteration in the systemic redox status [ 8 ]. In another retrospective study in France by Schmitt et al that enrolled 15 pregnant women with and without COVID-19 during their third trimester, no differences were shown between CRP levels and OS markers between groups [ 30 ]. Another report from Iran by Karkhanei et al including 96 individuals with and without COVID-19 found that elevation in serum levels of OS (reduced glutathione and TAC) and reduction of antioxidant indices (total oxidant status) could aggravate the disease's severity in hospitalized patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Sinaci et al [50] showed that the levels of vitamin D in pregnant women with moderate/severe courses of COVID-19 were lower (13.69 ng/mL) compared to those of pregnant women with a mild approach (13.69 ng/mL). In addition, Schmitt et al [51] obtained similar results. They showed that the level of vitamin D in pregnant women (patients and controls) was <20 ng/mL, while in the case of mild COVID-19, the level of vitamin D in pregnant patients was lower (<12 ng/mL) [51].…”
Section: Natural Antioxidants To Treat or Support Covid-19 Patients?mentioning
confidence: 68%
“…In addition, Schmitt et al [51] obtained similar results. They showed that the level of vitamin D in pregnant women (patients and controls) was <20 ng/mL, while in the case of mild COVID-19, the level of vitamin D in pregnant patients was lower (<12 ng/mL) [51].…”
Section: Natural Antioxidants To Treat or Support Covid-19 Patients?mentioning
confidence: 68%
“…In literature, a comparative case-control study in a pregnant population of 82 positive and 174 negative women (controls) suggested serum 25-vitamin D levels were significantly lower in positive pregnant women than in controls at the time of delivery [11]. However, as the main study limitation, only a single timing of blood collection was considered.…”
Section: Discussionmentioning
confidence: 99%
“…Schmitt et al have recently measured vitamin D levels and attempted to correlate them with the severity of COVID-19 [11]. They found that both positive and negative women had low levels of vitamin D in the third trimester.…”
Section: Introductionmentioning
confidence: 99%